Digital transformations in logistics operations: challenges and enables in fast moving consumer goods (FMCG) sector in Bangladesh - Hossain, Mohammed Imam (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master in Procurement and Supply Management, 2024.